The Former Presidential Lifetime Pension: A Critique of Its Application in Peru - Bravo Montalvo , Washington Luis (Revista de Derecho, 2025)
The pension or periodic economic benefit granted to a person for reasons such as retirement is a pension benefit that falls under social security, although its origins are closely related to labor law, and specifically to the nature of work and the worker. In this context, after reviewing its history and antecedents in Peru and in comparative law, which led to the establishment of a lifetime pension for former constitutional presidents in 1995 through Law N°. 26519, the objective of this work is to determine whether the lifetime pension, as such, constitutes a right derived from the work performed by a president of the Republic for the nation, or whether, on the contrary, it is simply a recognition of presidential dignity; regardless of whether this dignity has been called into question or undermined as a consequence of the beneficiary’s performance during their presidential term. We are interested in knowing what path this "right" or "benefit" has taken and whether, in any way, it has responded to the spirit that guided the law. Thus, we will study the legal nature of the lifetime pension, and its close correspondence with labor law and we will also address the figure of the former president of the Republic and his relationship with the quality of worker, contributing to the generation of a pension right, but also with the activity, properly, of government, within the framework of public administration, and, finally, we will review whether the lifetime pension should correspond to the presidential dignity.